Perspectives of infant active play: a qualitative comparison of working versus stay-at-home parents - Kailey Snyder; John P. Rech; Kim Masuda; Danae Dinkel (BMC, 2021)
Abstract Background Parents play a key role in infant's development through their interactions and the type of environment they provide to promote active play. The amount of time parents are able to spend with their infant is dependent on their working status, yet few studies have explored parent perception of their infant's active play by working status. The purpose of this study was to explore parent perception of active play and compare responses between working and stay-at-home parents. Methods Twenty-nine parents participated in this qualitative study by completing a one-time, in-person semi-structured interview based on the Theory of Planned Behavior. Themes were developed and compared based on parental working status using a directed content analysis approach. Results All parents believed active play could have a positive effect on their child's development through physical, social and emotional, cognitive, and/or language and communication development. However, stay-at-home parents reported a broader impact of active play across these domains; whereas working parents most often referenced active play as impacting infant's physical development. Social and emotional interactions were the highest reported form of active play among all parents. Additionally, all parents described similar barriers to increasing the time for active play. The most commonly reported barrier for all parents was time or schedule followed by care needs of the infant, environmental concerns, and need for restrictive devices (e.g., car seats). More stay-at-home parents than working parents reported the care needs of the infant as being a barrier. Recommendations for active play were not widely known amongst all parents, with a higher percentage of working parents reporting they would desire advice from a healthcare provider. Conclusions Working status of parents appears to have implications on perceptions of active play which in turn may influence infants' development. Future studies should objectively assess the impact of parents' working status on infant development and explore how gender of the parent may serve as a confounding variable.